The Impact of Preoperative Sarcopenia on Survival Prognosis in Patients Receiving Neoadjuvant Therapy for Esophageal Cancer: A Systematic Review and Meta-Analysis - Jin, Sheng-bo; Tian, Zi-bin; Ding, Xue-li; Guo, Ying-jie; Mao, Tao; Yu, Ya-nan; Wang, Kai-xuan; Jing, Xue (Frontiers in Oncology, 2021)
Background Sarcopenia is a poor prognostic factor in patients with esophageal cancer (EC). It can be aggravated by neoadjuvant therapy (NAT) that improves the prognosis of patients with EC. Until now, the impact of preoperative sarcopenia on survival prognosis in patients receiving NAT for EC remains unclear. Methods We systematically researched relevant studies in the PubMed, EMBASE, Web of Science, the Cochrane Library databases up to March 8, 2020. Prevalence of sarcopenia before and after NAT, overall survival (OS) and disease-free survival (DFS) were collected for analysis. Finally, eleven cohort studies were included. Results Pooled analysis indicated that preoperative sarcopenia was negatively associated with OS. (HR = 1.290; 95% CI [1.078–1.543]; P = 0.005; I2 = 0.0%) and DFS (HR = 1.554; 95% CI [1.177–2.052]; P = 0.002; I2 = 0.0%) in the patients with EC receiving NAT. The prevalence of sarcopenia increased by 15.4% following NAT (95%CI [12.9%-17.9%]). Further subgroup analysis indicated that sarcopenia diagnosed following NAT (HR = 1.359; 95% CI [1.036–1.739]; P = 0.015; I2 = 6.9%) and age >65 years (HR = 1.381; 95% CI [1.090– 1.749]; P = 0.007; I2 = 0.0%) were the independent risk factors for decreased OS. Conclusions Clinicians should strengthen the screening of preoperative sarcopenia in patients of EC both receiving NAT and older than 65 years and give active nutritional support to improve the prognosis of patients. Systematic Review Registration International Platform of Registered Systematic Review and Meta-Analysis Protocols (INPLASY), identifier INPLASY202050057.